Comparison of dry eyes parameters in postmenopausal women with and without honey supplement - Baharuddin, Noorlaila (2017)
Background Dry eyes is one of the most common ocular surface problems among elderly particularly among postmenopausal women due to hormonal imbalance. Ocular surface inflammation and tears hyperosmolarity are known pathogenesis of dry eyes. Objective The objective of this study is to compare the mean change (baseline and three months post treatment) in symptom [base on Ocular Surface Disease Index (OSDI) score] and signs (Schirmer test value and TBUT) between oral supplementation of honey cocktail and nonhoney groups among postmenopausal women. Methods A randomised interventional study was conducted from November 2015 to May 2017, at Hospital Universiti Sains Malaysia, Kelantan, Malaysia. The eligible postmenopausal women were randomised into 2 groups (honey cocktail group and non-honey group) by using random sampling envelope technique. Participants were assessed for OSDI score using OSDI questionnaire and evaluated for Schirmer test value and TBUT at baseline and at 3 months after daily oral supplementation of 20g honey cocktail. Statistical analyses were performed using SPSS version 22.0. Only right eye was chosen to analyse for standardization.Results A total of 60 postmenopausal women were recruited (30 participants in honey cocktail group and 30 participants in non-honey group). Honey cocktail group showed reduction of disability of OSDI score and improvement in Schirmer test value at 3 months post honey supplementation compared to non-honey group. There was no significant difference in mean change of OSDI score (p=0.644), Schirmer test value (p=0.372) and TBUT (p=0.471) between honey cocktail and non-honey groups. Conclusion Postmenopausal women with honey cocktail supplements shows better clinical response compared to non-honey group. However, there was no significant difference between the two groups. Further studies with longer duration of honey supplementation is recommended as honey have a slow effect. Oxidative stress and inflammatory markers are essential to establish the effect of honey supplements in postmenopausal women.